The comparison of ozone production with dielectric barrier discharge plasma reactors series and parallel at atmospheric pressure. (May 2019) - Kinandana, A W; Yulianto, E; Prakoso, A D; Faruq, A; Qusnudin, A; Hendra, M; Sasmita, E; Restiwijaya, M; Pratiwi, S H; Arianto, F; Nur, M
Abstract: Ozone that was generated by using dielectric barrier discharge plasma (DBDP) reactor has been investigated. In this study, we compared ozone production with reactor series and parallelled at atmospheric pressure. The reactor used models of a wire mesh - aluminum foil configuration. The first reactor uses a series circuit with two reactors and the second reactor uses a parallel circuit with two reactors. Ozone was produced by DBDP reactor using AC high Voltage. Oxygen that source of ozone has been taken from the pure oxygen and natural gas. Some analysis conducted including the variation of voltage, the flow rate of gas and type of source gas which affect produced concentration. Some parameters varied including voltage from 0 - 10 kV and the flow rate of gas 4 - 12 L / min. The results showed that ozone concentration in the series reactor is higher than that of the parallel reactor. The series reactor could produce ozone with a concentration of 348 ppm at a voltage of 10 kV. Then the parallel reactor of ozone could produce with a concentration of 240 ppm at a voltage of 10 kV. We found that series reactor could produce more high ozone concentration at the same voltage.